PARTISIPASI MASYARAKAT DALAM PELAKSANAAN PENDIDIKAN DI MADRASAH DINIYAH AWALIYAH (MDA) NUR ALIA DESA TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR - Namirah Azizah; Sumardi Sumardi; Desti Irja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The formulation of the problem in this research is how low the Participation of the Community in Implementation of Education in Madrasah Diniyah Awaliyah (MDA) Nur Alia Tarai Bangun Village Tambang Sub District Kampar Regency? And How much contribution contribution of Community Participation to Implementation of Education based on indicator which become factor In Madrasah Diniyah Awaliyah MDA Nur Alia Tarai Bangun Village Tambang Sub District Kampar? Benefits of this research is the contribution of thought to the Community Participation in the Implementation of Education At MDA Nur Alia Tarai Bangun Village Tambang District Kampar District. This research is descriptive with quantitative approach. The population in this study was 71 people. Sampling in this study using simple random sampling. The instrument used is a questionnaire containing 61 statement items. (2) energy, (3) ideas / thoughts, (4) material, and (5) ideas on community participation in education implementation at MDA Nur Alia Village Tarai Bangun Kecamatan Tambang Kabupaten Kampar is measured by indicators, fund. From the results of the research note that the contribution of thought to the Community Participation in the Implementation of Education At MDA Nur Alia Tarai Bangun Village Tambang Sub District Kampar included in the low category. with mean time indicator 2.16, mean power indicator 2.13, mean indicator ideas / thought 2.17, indicator of material material 2.13 and mean indicator fund 2.13, which still belong to low interpretation.Keywords: Community Participation in the Implementation of Education in MDA